Metaporus: a new look at communication - Dantas, Elenildes (2013)
This essay brings two proposals: an ontological one, of how to define communication as a happening and an epistemological one, of how to study the contemporary communicational phenomenon in its own movement, taking into consideration that we live in image or telematic society, created by the fourth bios, a coded world, from a programmed totalitarianism that imprisons us in a mirror cave, making us ‘tautistic’ and ‘dyslexic', eager to be machine, at the same time we suffer with horror vacui. Spectral society has become a place of this vacuum, where we only see ourselves and, talk to ourselves, in which the other completely disappears, an in which, also paradoxically, despite such a great technological progress in communication, nobody communicate themself.